Nutrition during pregnancy and lactation. - Figueroa, Rolando (2015)
The mammalian embryo is completely dependent on the mother for nourishment. It is absolutely necessary to maintain, at this stage of life, the right balance between circulating nutrients from the mother's blood. This biochemical normality depends on the diet of the mother, her nutritional reserves and their metabolic idiosyncrasies. Overall, the impact of abnormal nutrition depend on the level at which the nutritional factor acts, the specific nature and intensity of nutrient imbalance. The types of impacts are different: death, tissue abnormalities, growth retardation, abnormal cell differentiation and malformations. Therefore, improving the prognosis of pregnancy will depend in part on increased knowledge about nutritional requirements and to educate the community about the unwanted effects of nutrient deficiencies and excesses.